2020
DOI: 10.1186/s10194-020-01116-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of pain in general ageing populations: results from a multi-country analysis based on ATHLOS harmonized database

Abstract: Background: Pain is a common symptom, often associated with neurological and musculoskeletal conditions, and experienced especially by females and by older people, and with increasing trends in general populations. Different risk factors for pain have been identified, but generally from studies with limited samples and a limited number of candidate predictors. The aim of this study is to evaluate the predictors of pain from a large set of variables and respondents. Methods: We used part of the harmonized datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 93 publications
(112 reference statements)
6
11
0
Order By: Relevance
“…One important factor that may be associated with pain is the perceived health status of older adults. For example, a recent multi-country analysis found that, compared to good health, average-to-moderate self-rated health (odds ratio = 1.57) and poor health (odds ratio = 2.20) were significant predictors of pain among older adults [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…One important factor that may be associated with pain is the perceived health status of older adults. For example, a recent multi-country analysis found that, compared to good health, average-to-moderate self-rated health (odds ratio = 1.57) and poor health (odds ratio = 2.20) were significant predictors of pain among older adults [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, opioid use was common even for medical admissions with fewer days of hospital stay and younger ages. Conversely, high-dose MME/per day was not common among older patients, females, 24 and patients with lower leg fractures, and high CCI score as those patients usually demanded a higher daily MME/per day than their counterparts due to their pain severity levels. 25 The variations of opioid use among lower extremity fracture inpatients could be attributed to discordance in pain intensity, and ability to manage pain among orthopedic inpatients.…”
Section: Discussionmentioning
confidence: 93%
“…In the 2008 National Health and Wellness Survey in the UK, France, Italy, Germany, and Spain, the prevalence of moderate or severe pain in the adult population in the past month was 16.6% [6]. In a multicountry study among older adults, 39.5% developed pain between baseline and 5 years' followup [2]. In a national study that included people aged 60 and older in China, 32.5% reported having pain [7].…”
Section: Introductionmentioning
confidence: 99%
“…Te population in Tailand is rapidly ageing, increasing the health burden of older adults [1]. In the general population, pain is a common symptom, comorbid with clinical conditions, and the prevalence ranges from 10% to 60% [2]. Pain has been redefned by the International Association for the Study of Pain as "An unpleasant sensory and emotional experience associated with, or resembling that associated with, actual or potential tissue damage [3]."…”
Section: Introductionmentioning
confidence: 99%